Limited role for transforming growth factor–β pathway activation-mediated escape from VEGF inhibition in murine glioma models. Issue 12 (10th June 2016) - Mangani, Davide; Weller, Michael; Seyed Sadr, Emad; Willscher, Edith; Seystahl, Katharina; Reifenberger, Guido; Tabatabai, Ghazaleh; Binder, Hans; Schneider, Hannah
Abstract: Background: The vascular endothelial growth factor (VEGF) and transforming growth factor (TGF)–β pathways regulate key biological features of glioblastoma. Here we explore whether the TGF-β pathway, which promotes angiogenesis, invasiveness, and immunosuppression, acts as an escape pathway from VEGF inhibition. Methods: The role of the TGF-β pathway in escape from VEGF inhibition was assessed in vitro and in vivo and by gene expression profiling in syngeneic mouse glioma models. Results: We found that TGF-β is an upstream regulator of VEGF, whereas VEGF pathway activity does not alter the TGF-β pathway in vitro. In vivo, single-agent activity was observed for the VEGF antibody B20-4.1.1 in 3 and for the TGF-β receptor 1 antagonist LY2157299 in 2 of 4 models. Reduction of tumor volume and blood vessel density, but not induction of hypoxia, correlated with benefit from B20-4.1.1. Reduction of phosphorylated (p)SMAD2 by LY2157299 was seen in all models but did not predict survival. Resistance to B20 was associated with anti-angiogenesis escape pathway gene expression, whereas resistance to LY2157299 was associated with different immune response gene signatures in SMA-497 and GL-261 on transcriptomic profiling. The combination of B20 with LY2157299 was ineffective in SMA-497 but provided prolongation of survival in GL-261, associated with early suppression of pSMAD2 in tumor and host immune cells, prolonged suppression of angiogenesis, and delayed accumulation of tumor infiltrating microglia/macrophages. Conclusions: Our study highlights the biological heterogeneity of murine glioma models and illustrates that cotargeting of the VEGF and TGF-β pathways might lead to improved tumor control only in subsets of glioblastoma.